PENERAPAN AKUNTANSI SYARIAH ZISWAF BERDASARKAN PSAK109 - Pratama, Rifki Danu; Ilma, Aidah Nur; Shohibus Shulton, Muhammad; Rohmat, Syarif; Afandy, Saiful; Latifah, Eny (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
The purpose of this study was to determine the extent to which Sharia Financial Institutions apply sharia accounting to Zakat, Infaq, Shadaqoh, and Waqf by adjusting those in PSAK 109. The research method used is qualitative type of literature by using reference sources both from books, articles, journals and others to obtain the necessary information and data by analyzing more deeply. The results of the study are that there are still many Sharia Financial Institutions (LKS) that have not implemented PSAK 109, some LKS still use simple financial reporting so that the form and format of reporting for each LKS is different. The factor causing the non-application of PSAK 109 in some LKS is the difficulty in applying it due to the constraints of human resources owned by LKS. So that to overcome these problems, training and assistance are needed for LKS related to the application of PSAK 109. In addition to making disclosures about zakat, infaq. LKS also discloses the existence of non-halal funds and policies on the name of the receipt of funds, the reasons and the amount of these non-halal funds. LKS also discloses amil performance on the receipt and distribution of zakat and infaqfunds.